Analisis Pengaruh Motivasi Spiritual, Pengendalian Diri dan Sikap Tanggung Jawab terhadap Etos Mengajar serta Implikasinya pada Kebermaknaan Hidup dalam Perspektif Islam - Suliwati; Naqiyah Mukhtar (Jurnal Riset Madrasah Ibtidaiyah, 2022)
The purpose of this study was to analyze the level of spiritual motivation, self-control, the attitude of responsibility, meaning of life, and teaching ethos, as well as to prove the influence between variables in research, contributions, and predictions of research variables. This study uses a quantitative approach and the respondents are teachers at Elementary School Plus Tahfizhul Qur'an (PTQ) Annida Salatiga in 2021. The results of this study are (1) there is an influence between spiritual motivation, self-control, and attitude of responsibility towards teaching ethos with a positive significance value of 0.000. (2) The meaning of life in an Islamic perspective can strengthen the influence between spiritual motivation, self-control, and a responsible attitude towards teaching ethos with the acquisition of a positive significance value of 0.000. (3) The coefficient of determination of 0.938 indicates that 93.8% of teaching ethos can be explained from spiritual motivation, self-control, and responsibility, the remaining 6.2% is explained by other factors outside the model such as teacher competence, academic supervision, performance, and other factors. (4) The effective contribution of the meaning of life in an Islamic perspective can strengthen the influence of spiritual motivation, self-control, and a responsible attitude towards teaching ethos by 59.1%, this shows that the meaning of life in an Islamic perspective has a more dominant and very large influence than motivation. spirituality, self-control, and an attitude of responsibility.